The Effects of Students’ Motivational Factors on their Attitudes toward Mathematics - Samson Oyelola Oyedeji (Institute of Advanced Engineering and Science, 2017)
Mathematics is the only subject that cut across all sciences; hence the need for students’ positive attitudes toward mathematics cannot be under-estimated. Students’ motivation has been found to be having a positive relationship with the students’ attitudes toward mathematics. The aim of the study was to use path analysis to investigate the type of direct effects the motivational factors have on the students’ attitudes toward mathematics. To do this, twelve senior secondary schools were randomly selected from the Edo State South Senatorial District. Thirty students were randomly selected from each of the schools and a total of three hundred and sixty students were used for the study. A self-designed four-likert scale questionnaire titled “Students’ Motivational factors and Attitudes toward mathematics” was used to gather information from the subjects. Pearson Moment correlation and Regression analysis were used to analyse the data obtained from the questionnaire. The findings of the study revealed that intrinsic, home environment and teacher factors have positive direct effects on the students’ attitudes toward mathematics with intrinsic factor having the strongest and the most significant effect on students’ attitudes toward mathematics. The findings also revealed that peer group factor and school environment factor have negative effects on students’ attitudes toward mathematics. It was also discovered that all the motivational factors have positive and significant relationship with each other except intrinsic and school environment factors that have negative relationship with each other.